Pengaruh Pemberian Kompos TKKS Taspu Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis quineensis Jacq ) Pada Media Ultisol Di Polybag - Marpaung, Ridawati; Nengsih, Yulistiati; Bima, Bima (Jurnal Media Pertanian, 2024)
To support the successful development of oil palm nurseries, planting media fertility is needed. Ultisol planting media requires special treatment to improve the physical, chemical and biological properties of the soil. One of the activities to improve the fertility of ultisol soil is by applying organic fertilizer. The aim of the research was to determine the effect of TKKS Taspu compost fertilizer on the growth of oil palm seedlings and to determine the best dose of TKKS Taspu compost fertilizer for the growth of oil palm seedlings. The research was carried out from November 2023 to February 2024 at Telanai Pura and the Basic Laboratory of Batanghari University, Jambi. The environmental design used was a Completely Randomized Design (CRD) with one treatment : TKKS Taspu fertilizer (t) with four dose levels, t0 = 4 kg Ultisol/polybag (control), t1 = 600 g Taspu TKKS fertilizer + 3400 g Ultisol/polybag, t2 = 700 g Taspu TKKS fertilizer + 3300 g Ultisol/polybag, t3 = 800 g Taspu TKKS fertilizer + 3200 g Ultisol /polybag. The observation data was analyzed using Anova and the DNMRT test at a level of 5%. The parameters observed were ; plant height, stem diameter, shoot dry weight, root dry weight, seed quality index and water content of the planting medium. The results of the variance analysis showed that the application of Taspu TKKS compost fertilizer with t3 treatment (800 g Taspu TKKS fertilizer + 3200 g ultisol/polybag) was the right dose to support the growth of oil palm seedlings.